The potential of temporary shelters to increase survival of the endangered Mexican axolotl. Issue 6 (30th April 2021) - Ramos, Alejandra G.; Mena‐González, Horacio; Zambrano, Luis
Abstract: Amphibian populations worldwide are in decline. Proactive conservation techniques such as translocations into created and restored wetlands have gained popularity in recent years but may fail owing to high predation and low environmental adaptability. The Mexican axolotl ( Ambystoma mexicanum ), affected by rapid urbanization, is now possibly extinct in the wild despite millions living in captivity throughout the world. The aim of this study was to explore whether ponds from an artificial wetland can function as temporary shelters for a viable population of axolotls that could be re‐introduced into their native ecosystem in Xochimilco once it is restored. Egg‐laying and hatching of 11 unique axolotl pairs placed into reproductive enclosures and larval survival to 7 weeks and up to 12 months were examined. Physicochemical and biological parameters were estimated and compared among ponds. The results from this study are encouraging as they suggest that two ponds have adequate conditions for axolotls to reproduce and for larvae and juveniles to survive.